2014
DOI: 10.4103/1817-1737.134072
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and procalcitonin as biomarkers in mortality prediction of hospitalized patients with community acquired pneumonia

Abstract: INTRODUCTION:Community acquired pneumonia (CAP) may present as life-threatening infection with uncertain progression and outcome of treatment. Primary aim of the trial was determination of the cut-off value of serum interleukin-6 (IL-6) and procalcitonin (PCT) above which, 30-day mortality in hospitalized patients with CAP, could be predicted with high sensitivity and specificity. We investigated correlation between serum levels of IL-6 and PCT at admission and available scoring systems of CAP (pneumonia sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Compared to other earlier studies that used bacterial serology or blood culture for the diagnosis of pediatric pneumonia, or studies that used PCT assay that has relatively lower detection limits, our study successfully detected PCT concentrations in a wider range, and thus atypical and viral pneumonia can be distinguished from typical bacterial pneumonia [23]. To date, in spite of multiple pieces of evidence supporting the diagnostic and prognostic values for PCT, many studies have reported various prognostic factors for inflammatory diseases in adults or elderly patients [24][25][26]. However, only a few studies have assessed the role of PCT as a prognostic factor in pediatric pneumonia patients.…”
Section: Discussionmentioning
confidence: 78%
“…Compared to other earlier studies that used bacterial serology or blood culture for the diagnosis of pediatric pneumonia, or studies that used PCT assay that has relatively lower detection limits, our study successfully detected PCT concentrations in a wider range, and thus atypical and viral pneumonia can be distinguished from typical bacterial pneumonia [23]. To date, in spite of multiple pieces of evidence supporting the diagnostic and prognostic values for PCT, many studies have reported various prognostic factors for inflammatory diseases in adults or elderly patients [24][25][26]. However, only a few studies have assessed the role of PCT as a prognostic factor in pediatric pneumonia patients.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, IL-6 levels have been shown to have a good correlation with various clinical severity scores (e.g. PSI) [ 30 ]. Admission CRP < 100 mg/L has reduced risk for 30-day mortality, need for mechanical ventilation and/or inotropic support, and complicated pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the use of PCT for the prognostic prediction of hospitalized patients with respiratory infections, a cohort study from 2014 involving 101 hospitalized patients with CAP found results similar to those of the aforementioned studies; it showed that PCT had low to moderate accuracy for predicting 30-day mortality in this group of patients, with an AUC value of 0.66 (95%CI, 0.54 - 0.78; p ≤ 0.012) The best cutoff value found, 2.56ng/mL, presented a sensitivity of 76% and a specificity of 61.8% for predicting mortality. ( 35 ) Another prospective study involving 170 hospitalized patients with CAP showed the superior performance of initial PCT levels in predicting survival at 30 days (AUC for mortality, 0.8; 95%CI, 0.7 - 0.9), although it used a semiquantitative method to measure PCT. The accuracy of PCT was higher than that of other markers, including CRP; however, it was less accurate than the CURB-65 (AUC 0.88) and PSI (AUC 0.89) scores.…”
Section: Prognostic Value Of Procalcitonin In Lower Respiratory Tractmentioning
confidence: 99%